INCOME DISTRIBUTION of HOUSEHOLD RICE FARMERS in THE SIAM EPANG VARIETY in SERUYAN HILIR DISTRICT SERUYAN REGENCY - Lili Winarti; Rokhman Permadi (AGRIBEST, 2019)
Increased production of lowland rice from the Siam Epang variety  in Seruyan Hilir  Sub District is expected to increase income for farmer households, and in the production of each farmer - different because there are several influencing factors including land area, seeds, labor, amount of fertilizer, and the number of pesticides used, with the difference will affect the amount of income received by farmer households. The purpose of this study was to analyze the income distribution of households of Siam Epang rice farmers in Seruyan Hilir Sub District. This research method uses a survey method using a questionnaire to collect primary data, the number of respondents in this study were 86 respondents, to analyze family income distribution using the Gini Ratio coefficient and Lorenz curve to visually describe income distribution. Based on the results of the research described in the previous section, it can be concluded that the distribution of household income of rice farmers in the Siam Epang  variety in Seruyan Hilir  sub-district is 0.59, which means that farm household income is unevenly distributed and has high inequality.